Psychological characteristics of skeletal trauma and orthopedic patients in outpatient rehabilitation - T. A. Gubeidulina; Y. K. Rodygina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
With the biopsychosocial approach, in rehabilitation among other medical fields, the researchers’ interest in various social and psychological issues and their influence rose. The role of these factors in skeletal trauma and orthopedic care and rehabilitation is studied intensively and is important both for scientific and practical healthcare purposes. It is shown that some personality traits are connected to the results of skeletal trauma and orthopedic treatment. This original study was conducted to evaluate personality traits of skeletal trauma and orthopedic patients during their outpatient rehabilitation. The purpose of this study was to investigate the gender differences in personality traits of skeletal trauma and orthopedic patients to determine the medical communication strategies. 120 skeletal trauma and orthopedic patients during their outpatient rehabilitation (experiment sample) and 39 healthy individuals (control sample) were evaluated with the 16PF Questionnaire. After statistical analysis significant differences were found between the groups in B (reasoning) and Q4 (tension) factors; no other factors had significant differences in the groups. The factor B differences pointed out that concrete-thinking was more typical for the experiment group than for the control group. The factor Q4 differences meant tension was lower in skeletal trauma and orthopedic patients than in healthy individuals. The gender differences were as follows: extraversion, submissiveness, trusting, abstractedness, openness, and sensitivity were more characteristic for men, when women tended to be more introverted, dominant, suspicious, practical, diplomatic, and less sensitive.